2002
DOI: 10.1007/s00221-002-1075-z
|View full text |Cite
|
Sign up to set email alerts
|

Antisaccades and task-switching: interactions in controlled processing

Abstract: Smaller latency costs for switching from dominant (habitual) to non-dominant (unusual) tasks compared to the reverse direction have been noted in some studies of task-switching. This asymmetry has been cited as evidence of inhibitory effects from the prior trial. We examined accuracy and latency costs of task-switching between prosaccades and antisaccades, where task-switching is limited to stimulus-response re-mapping and occurs between tasks highly asymmetric in dominance. Eighteen subjects executed prosacca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
78
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 34 publications
15
78
1
Order By: Relevance
“…The participants exhibited the predicted switch benefit in antisaccade latency when required to switch between anti-and prosaccade trials (mixed-task block), as compared with when they completed anti-and prosaccade tasks separately in blocks of repeated trials (single-task blocks). The paradoxical improvement in antisaccade latency is consistent with the results of previous research (e.g., Barton et al, 2002;Cherkasova et al, 2002;Hodgson et al, 2004;Manoach et al, 2002), in which similar paradoxical reductions in antisaccade latencies were reported when participants were required to switch.…”
Section: Discussionsupporting
confidence: 91%
“…The participants exhibited the predicted switch benefit in antisaccade latency when required to switch between anti-and prosaccade trials (mixed-task block), as compared with when they completed anti-and prosaccade tasks separately in blocks of repeated trials (single-task blocks). The paradoxical improvement in antisaccade latency is consistent with the results of previous research (e.g., Barton et al, 2002;Cherkasova et al, 2002;Hodgson et al, 2004;Manoach et al, 2002), in which similar paradoxical reductions in antisaccade latencies were reported when participants were required to switch.…”
Section: Discussionsupporting
confidence: 91%
“…However, the association was not observed on trials after prosaccade. It has been argued that response slowing on trials after antisaccade is due to a carryover of a general inhibitory control mechanism over a saccade response system rather than due to requirement of inhibiting a previous task set (Cherkasova et al, 2002;Barton et al, 2006). The effective connectivity pattern that we observed in the present study may reflect such a carryover of an inhibitory control mechanism subserved by the neural network involving the FEF.…”
Section: Persistent Effective Connectivity Is Responsible For Responssupporting
confidence: 43%
“…In a Stroop paradigm in which subjects switch between automatic word reading and controlled color naming tasks, a greater switch cost is observed on a word-reading trial after color naming than on a color-naming trial after word reading (Allport et al, 1994). Also, when switching between prosaccade and controlled antisaccade, that is, when switching between rules to make a saccade to and away from a visual target, a greater switch cost is observed on a prosaccade trial that follows an antisaccade trial than on an antisaccade trial that follows a prosaccade trial (Cherkasova et al, 2002;Fecteau et al, 2004;Barton et al, 2006). Moreover, responses become faster when switching from prosaccade to antisaccade than when repeating antisaccade.…”
Section: Introductionmentioning
confidence: 99%
“…This antisaccade switch benefit has been observed in a number of studies (e.g., Hodgson, Golding, Molyva, et al, 2004;Experiment1;Cherkasova, Manoach, Intriligator & Barton, 2002) using a variety of mixed antisaccade paradigms. This antisaccade switch benefit has been argued to reflect a greater allocation of attentional resources in the more attention demanding switch trials (Kristjansson, Chen, & Nakayama, 2001).…”
Section: Mixed Antisaccade Paradigmmentioning
confidence: 52%